Did zoom bomb? Negative video conferencing meetings during COVID‐19 undermined worker subjective productivity. Issue 5 (2nd November 2021) - Okabe‐Miyamoto, Karynna; Durnell, Eric; Howell, Ryan T.; Zizi, Martin
Abstract: The COVID‐19 pandemic forced workers to pivot to working from home (WFH), shifting from a dominantly offline to a dominantly online workplace, often conducting this shift to online work using video conference meetings. Although businesses tried to seamlessly continue business using video conferencing, research on how productivity has changed during the pandemic has been mixed. To better understand how productivity has been impacted during the pandemic, despite decades of research prior to the pandemic demonstrating the effectiveness of WFH, we conducted three quantitative and qualitative studies with workers from April 2020 to April 2021. Workers who reported video conferencing feeling like a forced interaction also reported dramatic levels of low subjective productivity through increased feelings of video conferencing anxiety (Studies 1–3). Qualitative reports of why workers felt forced to video conference identified feeling pressured by employers to use video and meetings being used as surveillance (Study 1b). However, some workers reported positive experiences while video conferencing, which was related to greater subjective productivity (Study 2). For workers who had video conference and face‐to‐face meetings, video conference meetings feeling like a forced interaction was still associated with lower subjective productivity through increased feelings of anxiety (even when controlling for face‐to‐face meetings feeling like a forced interaction; Study 3). Because WFH may last beyond COVID‐19, organizations and managers should allow workers to use audio instead of video during meetings and refrain from using video conferencing meetings to surveil their employees to ensure workers are reporting that they are remaining productive.